Classification of Human Failure in a Pharmaceutical Industry and its Various Corrective and Preventive Action – A Case Study on the Lessons Learned From the Past - Alavandar, Yudhistra Kumar (European Journal of Life Safety and Stability (2660-9630), 2023)
The incident / Accident in the pharmaceutical company is a major concern in the modern world. It is very important to know the various causes of the injury / accident while handling the deadly chemicals in the pharmaceutical sector. The collection of data for the incidents / accidents will help us to learn lessons from the past. The incident / Accident data is collected from the pharmaceutical industry from October 2017 to September 2021 in the Attibele, Bangalore, southern part of India. During the period there were 20 recorded incident / accident in the factory. Human failure for the classification for the various incidents / accidents are classified based on the Error by humans and violations in the seven different blocks, these are further classified as minor, major and dangerous. The percentage of the failure of the cause of the incident / accident are presented in the article. The incidents/ accidents were reported in the intermediate block > outside Intermediate block > Finished goods block > Pilot plant = Research & development block = Stores area = Effluent treatment plant area. These types of incidents / accidents, which were minor occurrences are two numbers, major and dangerous occurrences are five and thirteen numbers, which is a major cause of the concern. The human failures are responsible for the incident / accident. Its percentage, which varied from 5 (Routine and slip) % to 37.5 (Lapses) %. Various corrective and preventive action for each of the incident / accident has been presented. The human failures can be avoided by adopting strict safety rules and regulation in all the concern departments.